The Lost Submarines of Pearl Harbor - Delgado, James P.; Van Tilburg, Hans (Book collections on Project MUSE., 2016)
In the pre-dawn darkness of December 7, 1941, five Imperial Japanese Navy submarines surfaced off the coast of Oahu. Secured to the decks of these vessels were secret weapons to be deployed for the first time in modern warfare: two-man midget submarines, intended to enter Pearl Harbor without being detected and torpedo the US Navy battleships lying at anchor there. None of them would return from their mission. "One of the last remaining and persistent mysteries of the Pearl Harbor attack is that of the Japanese Midget Submarines. It is a fascinating story of innovation, courage, secrets, and failed expectations. And it is not only a story of the morning hours of December 7, but of the years before to develop these weapons and the years after, where they were deployed in the great Pacific War and how they fared as weapons of war." These words by Daniel J. Basta, from the foreword of this work, capture both the essence and the impact of The Lost Submarines of Pearl Harbor. James P. Delgado and his coauthors have worked on the story of these incredible craft for decades. They combed the records of the US Navy and the recollections of its veterans as well as Japanese, Australian, and British archives in order to uncover the truth. They have logged hours of direct observation and research on the midget subs in their final resting places, in some cases more than 1,000 feet below the surface of the Pacific. And in the end, they have woven a tapestry of scholarship, historical sleuthing, scientific insight, and good storytelling that will enthrall specialists and history enthusiasts alike.